If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + X = 4 Solving 25 + X = 4 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + X = 4 + -25 Combine like terms: 25 + -25 = 0 0 + X = 4 + -25 X = 4 + -25 Combine like terms: 4 + -25 = -21 X = -21 Simplifying X = -21
| 2(3x-1)+7=9-x | | 3xy-3yx= | | 2x-14=-2(x+3)-3 | | 3/4a=1/4 | | X=12z | | (d^3+1)y=0 | | Ix+2l=3 | | 12=4!x^(1/2) | | 12=4!x(1/2) | | 3z-5=p | | (4+8x)=10 | | 48/][587 | | 150x2/3 | | 12x+40x=572 | | 5(2x-1/25) | | cosx-(x/4)=0 | | 203=3.14*x^2 | | B=45a-7b | | cos(x)=0.5*cos(0.5*x) | | X^2-7x=-30 | | 7cosx+sinx=-5 | | 2*cos(x)-cos(0.5x)=0 | | 12*4x= | | 0.75/x=0.6 | | 5w=12w+14 | | 1/2X+6/2=3/2 | | (4X-20)(-5x+7)=0 | | X=(x*0.17)+5720 | | 6x+3=-17+2x | | 2(3x-5)=38 | | 24-3x=16-2y | | 2k^2-16k+12=0 |